Microwave-assisted solvothermal: An efficient and new method to obtain hydrophobic wood surfaces - Zanatta, Paula; Luiz Missio, André; Lazarotto, Marília; da Silva Cava, Sérgio; Lovato Gomes Jardim, Pedro; Alberto Gatto, Darci; Lúcio Moreira, Mário (Maderas. Ciencia y Tecnología, 2018)
The objective of this work was to form a hydrophobic surface in a highly porous wood by coating and incorporating TiO2 micro/nano structures through the microwave-assisted solvotermal method, without need any pre- or post-modification of the wood substrate, using low temperatures and short times. The behavior and morphology of the TiO2-treated surfaces was characterized using scanning electron microscopy (SEM), while the elemental composition was determined via energy-dispersive X-ray spectroscopy and X-ray diffraction analysis. The results indicated that the crystallization of the TiO2 anatase phase was efficient and fully coated the wood surface during the solvothermal process. The treated wood contained TiO2 particles with an average diameter of 200 nm that also allowed to coat an abundant fraction of tracheids cell walls. When investigated through X-ray spectroscopy-mapping, the element titanium appeared abundantly throughout the wood. After TiO2 growth in wood through the microwave-assisted solvotermal method, a roughness at the micro/nano scales structures was created on the wood surface, originating an increase in the contact angle up to 137°, which characterizes the appearance of a hydrophobic surface. The TiO2-treated wood demonstrated 85% of water absorption after 400 hours of immersion, while untreated wood reached 160%, suggesting that the microwave-assisted solvotermal process promotes a delay in the progression of water absorption. This feature can improve the dimensional stability of wood, contributing to the increase of its durability and applications.